PENGARUH BUDAYA KERJA TERHADAP KESELAMATAN KESEHATAN KERJA DINAS PEMADAM KEBAKARAN KOTA PADANG - Afrinia Winriyani; Aldri Frinaldi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
This research is based on the problems of work culture and occupational health safety of the padang city fire service. The purpose of this study is to analyze how much the influence of work culture on occupational health safety of padang fire service. This research used quantitative method, with descriptive technique. The technique sampling was done by purposive sampling. Quantitative data is collected using Likert Scale numbers that have been tested for validity and reability. The population of the sample is 120 employees. In this study, it can be seen that there is a positive effect of work culture on occupational health safety of the padang city fire service that has been tested with a value, and obtained a small significance value of 0.000 out of 0.05 and the percentage contribution of variable X to Y of 37.1%. The value listed in this study is that the better the work culture, the better it can shape the safety of occupational health. This research was conducted to improve the cultural aspects of work in improving the occupational health safety of the padang city fire service.